2009
DOI: 10.2308/iace.2009.24.1.13
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Professional Context on Accounting Students' Moral Reasoning

Abstract: This study investigates whether the professional context of accounting ethical dilemmas influences accounting students' moral reasoning. In a between-subjects experiment, 101 accounting students from a large public AACSB-accredited university in the U.S. responded to four ethical dilemmas faced by either auditors or corporate accountants designed to measure their deliberative moral reasoning. As expected, students in the audit condition exhibited significantly higher deliberative moral reasoning than students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
2
17
1
Order By: Relevance
“…Of the control variables, only work experience had a significant association to higher levels of moral reasoning (p = 0.008). Although Fleming et al (2009) found a significant positive association between years of accounting experience and moral reasoning, our results indicate that general work experience may be the influencing factor that affects moral reasoning. …”
Section: Resultscontrasting
confidence: 97%
See 2 more Smart Citations
“…Of the control variables, only work experience had a significant association to higher levels of moral reasoning (p = 0.008). Although Fleming et al (2009) found a significant positive association between years of accounting experience and moral reasoning, our results indicate that general work experience may be the influencing factor that affects moral reasoning. …”
Section: Resultscontrasting
confidence: 97%
“…The context in which the educational process is framed is important. In a study conducted by Fleming et al (2009), the ethical component of the educational process was grounded in an audit setting, which was compared to an educational process in a general accounting context. Similar to the studies listed above, the ethics content included in their auditing course may have led to a greater level of moral reasoning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They also had an average of 38.7 months of general business experience and 2.4 months of audit experience. Prior to this, research has used accounting students to proxy for entry-level accountants (e.g., Massey and Thorne 2006;Fleming et al, 2009), and the demographic characteristics of this sample suggest that the participants are reasonable proxies for entry-level auditors. Table 1 presents demographic data for the sample.…”
Section: Research Methods Samplementioning
confidence: 99%
“…They provide evidence that the U.S. CPAs had significantly higher deliberative ethical reasoning than their Canadian counterparts. Fleming et al (2009) compared U.S. accounting students' deliberative ethical reasoning scores on the AEDI to a version of the instrument adapted for the management accounting context, and found deliberative ethical reasoning to be higher in the audit context. Also, of special significance to the current study, Ge and Thomas (2008) found that Canadian accounting students exhibited higher audit-specific deliberative ethical reasoning than Chinese accounting students.…”
Section: Measuring Accountants' Ethical Reasoningmentioning
confidence: 98%